1975
DOI: 10.1104/pp.55.5.937
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Indole-3-acetic Acid and Other Growth Regulators on the Ripening of Avocado Fruits

Abstract: Observations were made of the effects of several plant regulators, indole-3-acetic acid, kinetin, abscisic acid, and gibberellic acid, as well as of extracts prepared from leaves and fruit stalks on the respiration pattern, ethylene production, and the number of days to ripen of avocado fruits (Persea americana Mill.).These substances were vacuum infiltrated to insure good penetration and distribution. Kinetin, abscisic acid, gibberellic acid, and the extracts had no effect on either ripening time or on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

1980
1980
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 18 publications
(29 reference statements)
0
22
0
2
Order By: Relevance
“…We observed that when G. xylinus was grown in the presence of IAA, pellicles were thin ( Figure 2A) and of low cellulose content ( Figure 2C). This result can be explained in context of a plantmicrobe interaction: elevated auxin levels in the plant delay ripening and senescence, 28,[48][49][50] as a result, the sugars available for bacterial cellulose synthesis will be lower compared to ripened fruit. Exogenous IAA impedes G. xylinus cellulose synthesis yet stimulates growth rate so that cellular density is at a peak when the fruit ripens and glucose becomes more readily available.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that when G. xylinus was grown in the presence of IAA, pellicles were thin ( Figure 2A) and of low cellulose content ( Figure 2C). This result can be explained in context of a plantmicrobe interaction: elevated auxin levels in the plant delay ripening and senescence, 28,[48][49][50] as a result, the sugars available for bacterial cellulose synthesis will be lower compared to ripened fruit. Exogenous IAA impedes G. xylinus cellulose synthesis yet stimulates growth rate so that cellular density is at a peak when the fruit ripens and glucose becomes more readily available.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in which tomato fruit (climacteric) were used in culture (Cohen, 1996) have given further credence to earlier observations that elevated auxin levels can delay ripening. Auxins have also been shown to affect the ripening of a number of nonclimacteric fruit, including avocado (Tingwa and Young, 1975), bananas (Vendrell, 1969), pear (Frenkel and Dyck, 1973), and strawberry (Fruguriu anunussa L.; Given et al, 1988). Strawberries, in particular, provide a useful experimental system because the achenes, which are the source of the auxins involved in ripening, can be removed.…”
mentioning
confidence: 99%
“…In addition to C 7 sugars as ripening inhibitors of the fruit while on the tree, endogenous levels of auxins in the fruit have been reported during the early seventies as the resistant factor in ripening of avocado [53,54]. The application of exogenous auxins to the fruit stimulated ethylene production and accelerated ripening, but if auxins are infused into the fruit tissue by the vascular system, ethylene levels are limited and ripening is inhibited.…”
Section: Phytohormones (Endogenous and Exogenous Application)mentioning
confidence: 99%
“…Ripening processes are highly dependent on continuous protein synthesis to provide substrates/intermediates to key metabolic pathways such as ethylene biosynthesis and respiration [37]. The ripening process can be affected by many factors including: water movement, phytohormones, mineral nutrition, carbohydrates and ripening enzymes [38][39][40][41][42]. As a climacteric fruit, avocado ripening is characterized by an increase in the respiration rate accompanied by an increase in ethylene production.…”
Section: Avocado Fruit Ripening Physiologymentioning
confidence: 99%